2021
DOI: 10.1242/jeb.243016
|View full text |Cite
|
Sign up to set email alerts
|

How to build a puncture- and breakage-resistant eggshell? Mechanical and structural analyses of avian brood parasites and their hosts

Abstract: Evolved eggshell strength is greater in several lineages of obligate avian brood parasites (birds that lay their eggs in other species’ nests) compared to their hosts. Greater strength is typically indirectly implied by eggshell thickness comparisons between parasites and hosts. Nevertheless, there is strong evidence that the eggshell structural organization differentially influences its mechanical properties. Using instrumental puncture tests and SEM/EBSD and XRD techniques, we studied the most relevant eggsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 108 publications
1
5
0
Order By: Relevance
“…Comparing EFEM with the crystal orientations (texture or non-texture) of six avian species (Table 2 and Figure S2), we found that the orientation of calcite crystals appears to have no effect on EFEM. This is consistent with the result of López's study [47], and may be explained by the fact that EFEM measures the effective (or average) stiffness of a finite volume of eggshell that consists of many differently oriented grains. If the number of grains is large and their orientations are random enough, then variations in stiffness with individual grains may be cancelled out.…”
Section: Crystallographic Analysis Using Ebsdsupporting
confidence: 91%
“…Comparing EFEM with the crystal orientations (texture or non-texture) of six avian species (Table 2 and Figure S2), we found that the orientation of calcite crystals appears to have no effect on EFEM. This is consistent with the result of López's study [47], and may be explained by the fact that EFEM measures the effective (or average) stiffness of a finite volume of eggshell that consists of many differently oriented grains. If the number of grains is large and their orientations are random enough, then variations in stiffness with individual grains may be cancelled out.…”
Section: Crystallographic Analysis Using Ebsdsupporting
confidence: 91%
“…Compared to palaeognath eggshells, neognath eggshells are characterized by: (i) comparatively weak vertical c -axis alignment (see Appendix 3 for selected neognath eggshells; Grellet-Tinner et al, 2017 ; Choi et al, 2019 ; López et al, 2021 ; Chiang et al, 2021 ; see also Oser et al, 2021 for a similar case of Mesozoic egg); (ii) boundary between ML and SqZ is not easily identified because of prismatic shell units ( Mikhailov, 1997a ). However, SqZ of common murre ( Uria aalge ) (Charadriiformes) eggshell is similar to that of rhea-style palaeognath eggshell in that ‘splaying’ is clear ( Appendix 3—figure 4 ) and the overall structure of European green woodpecker ( Picus viridis ) eggshell ( Appendix 3—figure 5 ) is remarkably similar to that of tinamou-style palaeognath eggshell.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, mechanical strength of eggshell is an important factor for the reproductive biology of every oviparous amniote. Experimental compression or simulation studies have shown that eggshell thickness has a positive correlation with the strength of eggshells ( Ar et al, 1979 ; Hahn et al, 2017 ; Juang et al, 2017 ; López et al, 2021 ), and this relationship may even provide a way to infer contact incubation in Palaeognathae (including extinct taxa; Huynen et al, 2010 ; Yen et al, 2021 ) as well as laying process of Palaeognathae ( Sellés et al, 2019 ). However, López et al, 2021 showed that microstructures, which was usually not considered in earlier studies such as finite element method, of avian eggshell can further contribute to the strength of the eggshells.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to palaeognath eggshells, neognath eggshells are characterized by: (i) comparatively weak vertical c -axis alignment (see Appendix 1—Figures 4–8 for selected neognath eggshells; Grellet-Tinner et al, 2017; Choi et al, 2019; López et al, 2021; see also Oser et al, 2021 for a similar case of Mesozoic egg); (ii) boundary between ML and SqZ is not easily identified because of prismatic shell units (Mikhailov, 1997b). However, SqZ of common murre ( Uria aalge ) (Charadriiformes) eggshell is similar to that of rhea-style palaeognath eggshell in that ‘splaying’ is clear (Appendix 1—figure 7) and the overall structure of European green woodpecker ( Picus viridis ) eggshell (Appendix 1—figure 8) is remarkably similar to that of tinamou-style palaeognath eggshell.…”
Section: Resultsmentioning
confidence: 99%